2015
DOI: 10.4236/ce.2015.621231
|View full text |Cite
|
Sign up to set email alerts
|

Variables Affecting the Creativity of Undergraduate Students at Nakhon Ratchasima Rajabhat University

Abstract: This descriptive research aims to investigate the construct validity of selected variables affecting the creativity of undergraduate students at Nakhon Ratchasima Rajabhat University. Seven hundred and sixty students participated in this study. They were tested on items relating to their creativity. The results showed that executive administration, teaching, instructional attitudes, motivation, and personality variables affected the creativity of the undergraduates. Creativity consisted of originality, fluency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Boonchan, Pupat, & Seesan, 2015;Kharkhurin & Samadpour Motalleebi, 2008;Pan & Yu, 2016). This is commonly measured through verbal statements and/or graphs corresponding to symbolic expressions made by language units (words, lines), where their combination of meanings are easily grasped.…”
Section: Assessing Creative Process In College Studentsmentioning
confidence: 99%
“…Boonchan, Pupat, & Seesan, 2015;Kharkhurin & Samadpour Motalleebi, 2008;Pan & Yu, 2016). This is commonly measured through verbal statements and/or graphs corresponding to symbolic expressions made by language units (words, lines), where their combination of meanings are easily grasped.…”
Section: Assessing Creative Process In College Studentsmentioning
confidence: 99%
“…Some of these studies have demonstrated the importance of faculty members' development for creativity (15,16). Several studies have also focused on student creativity, its fostering methods, and factors affecting it (17,18). Some studies have focused on educational factors and the relationship between them and creativity.…”
Section: Introductionmentioning
confidence: 99%
“…This task attracts special attention of scientific researchers all over the world. Many authors are interested in clarifying the factors influencing formation and development of creativity among students (Sadeghi & Ofoghi, 2011;Powel & Carrol, 2013;Boonchan et al, 2015). There are many factors influencing formation and development of creative activity among students.…”
Section: Introductionmentioning
confidence: 99%